Violence and stigma: a qualitative exploration of judicial perceptions of defendants with psychiatric disorders - Simonsson, Peter (Psychology, crime & law, 2024)
Judges have significant decision-making power that dictates the outcomes of defendants, but their perceptions regarding persons with psychiatric disorders (PPDs) are understudied. This qualitative study explored judges’ perceptions of dangerousness of PPDs and the benefits and risks of violence surrounding the use of community-based interventions for PPDs. Semi-structured interviews were conducted with 31 state and city-level court judges, which were then thematically analyzed. Results show that judges perceived PPDs as a risk to public safety; specifically, they perceived psychiatric disorders as enhancing the risk for violent behaviors. Although judges generally expressed positive views of psychiatric services, they had concerns about the decline in institutional care, indicating a need to enhance social control mechanisms for PPDs. Results suggest the need for policies to address institutional stigma in court settings and judicial trainings about the primary factors associated with crime and violence related to this population. At the same time, it is essential to recognize the obligatory responsibility of mental health providers to treat and advocate for their clients and to understand the procedures of the criminal justice system.